Local ablative radiotherapy for oligometastatic non-small cell lung cancer - Suh, Yang-Gun (Radiat Oncol J, 2019)
In metastatic non-small cell lung cancer (NSCLC), the role of radiotherapy (RT) has been limited to palliation to alleviate the symptoms. However, with the development of advanced RT techniques, recent advances in immuno-oncology therapy targeting programmed death 1 (PD-1) and programmed death ligand 1 (PD-L1) and targeted agents for epidermal growth factor receptor (EGFR) mutation or anaplastic lymphoma kinase (ALK) translocation allowed new roles of RT in these patients. Within this metastatic population, there is a subset of patients with a limited number of sites of metastatic disease, termed as oligometastasis that can achieve long-term survival from aggressive local management. There is no consensus on the definition of oligometastasis; however, most clinical trials define oligometastasis as having 3 to 5 metastatic lesions. Recent phase II randomized clinical trials have shown that ablative RT, including stereotactic ablative body radiotherapy (SABR) and hypofractionated RT, to primary and metastatic sites improved progression-free survival (PFS) and overall survival (OS) in patients with oligometastatic NSCLC. The PEMBRO-RT study, a randomized phase II study comparing SABR prior to pembrolizumab therapy and pembrolizumab therapy alone, revealed that the addition of SABR improved the overall response, PFS, and OS in patients with advanced NSCLC. The efficacy of RT in oligometastatic lung cancer has only been studied in phase II studies; therefore, large-scale phase III studies are needed to confirm the benefit of local ablative RT in patients with oligometastatic NSCLC. Local intensified RT to primary and metastatic lesions is expected to become an important treatment paradigm in the near future in patients with metastatic lung cancer.